2017
DOI: 10.1002/cite.201600134
|View full text |Cite
|
Sign up to set email alerts
|

Simplified, High Drug‐Loaded Formulations Containing Hydrochlorothiazide for Twin‐Screw Granulation

Abstract: Simplified, high drug loaded formulations for use in twin-screw granulation and tableting were introduced, using the plastically deforming drug ibuprofen. This concept was enlarged by application of hydrochlorothiazide, because opposed deformation behavior was expected to result in different product performances. In most instances the results differed. Critical quality attributes like granule size distribution, disintegration time, and tensile strength of tablets could be met. The study confirms the suitabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Therefore, more research is required in the field of simplified formulations. This concept was originally studied by Meier et al for formulations containing 90% ibuprofen [ 22 ] and was later applied to a high-dosed hydrochlorothiazide formulation [ 106 ]. Recently, Vanhoorne et al demonstrated that delta mannitol could be used as a suitable filler and binder for granulating 75% paracetamol [ 60 ].…”
Section: Recommendations and Research Opportunitiesmentioning
confidence: 99%
“…Therefore, more research is required in the field of simplified formulations. This concept was originally studied by Meier et al for formulations containing 90% ibuprofen [ 22 ] and was later applied to a high-dosed hydrochlorothiazide formulation [ 106 ]. Recently, Vanhoorne et al demonstrated that delta mannitol could be used as a suitable filler and binder for granulating 75% paracetamol [ 60 ].…”
Section: Recommendations and Research Opportunitiesmentioning
confidence: 99%
“…Compatibility studies such as screening drug-excipient incompatibilities are routinely required to identify (7). In continuous manufacturing, from a regulatory perspective, each batch of excipients and APIs needs to be tracked to know its contribution to each produced unit (8).…”
Section: Author Accepted Manuscriptmentioning
confidence: 99%